2010
DOI: 10.3390/molecules15095971
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Potential of Lavandula x intermedia Emeric ex Loisel. 'Budrovka': A Comparative Study with L. angustifolia Mill.

Abstract: A Croatian indigenous cultivar of lavandin, Lavandula x intermedia ‘Budrovka’ (Lamiaceae) was studied for the phenolic acids, flavonoids, anthocyanins, procyanidins and total tannins, as well as total polyphenols content, in the flower, inflorescence stalk and leaf ethanolic extracts. Antioxidant potentials on these plant part extracts were assessed by the DPPH free radical scavenging activity, iron chelating activity, reducing power, lipid peroxidation inhibition properties and total antioxidant capacity assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 32 publications
4
46
0
1
Order By: Relevance
“…7). The strongest antioxidant activity of the tested samples was shown by the extract from dried in vitro plants of 'Ellagance Purple' -37.4 mg TE g -1 DW, whereas the weakest activity was exhibited by the extract from dried Blažeković et al (2010), the antioxidant activity is higher in the stems than in the leaves. Robu et al (2012) had tested extracts of L. angustifolia 'Munstead' and noted that the free radical scavenging activity, measured using the DPPH method for the concentration of 2.5 mg ml -1 , was 21.41%.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 86%
See 1 more Smart Citation
“…7). The strongest antioxidant activity of the tested samples was shown by the extract from dried in vitro plants of 'Ellagance Purple' -37.4 mg TE g -1 DW, whereas the weakest activity was exhibited by the extract from dried Blažeković et al (2010), the antioxidant activity is higher in the stems than in the leaves. Robu et al (2012) had tested extracts of L. angustifolia 'Munstead' and noted that the free radical scavenging activity, measured using the DPPH method for the concentration of 2.5 mg ml -1 , was 21.41%.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 86%
“…Essential oils, extracts and dried plants of lavender have been studied for their antioxidant activity using the DPPH, FRAP and ABTS methods (Lee and Shibamoto 2002, Blažeković et al 2010, Hui et al 2010, Spiridon et al 2011, Hamad et al 2013, Proestos et al 2013. Examinations of the capability to scavenge DPPH free radicals demonstrated that extracts from dried in vitro plants of all the tested cultivars were characterized by significantly higher antioxidant activity than extracts of dried fieldgrown plants (Tab.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…Total phenolic content determination was performed according to the FolinCiocalteu method as described by Blažeković et al (2010). Briefly, 50 μL of the test sample mixed with 2.4 mL distilled water and 200 μL of Folin-Ciocalteu's reagent (1/10) were added to 200 μL of Na 2 CO 3 20 %.…”
Section: Chemicalsmentioning
confidence: 99%
“…Vanillin and proanthocyanidin assays are usually used to estimate total procyanidinidins (condensed tannin), while hydrolysable tannins can be quantified by the potassium iodate method (Dai & Mumper, 2010;Hartzfeld et al, 2002). Determination of phenolic acids can be performed by the method described in European Pharmacopoeia using nitrite-molybdate reagent of Arnow which forms complexes with ortho-diphenols (Blažeković et al, 2010;EDQM, 2006). On the other hand, complexation of the phenolics with Al(III) is the principle of spectrophotometric assay used for quantification of total flavonoids (Jurišić Grubešić et al, 2007;Vladimir-Knežević et al, 2011).…”
Section: Phytochemical Characterization Of Polyphenolsmentioning
confidence: 99%
“…Polyphenols were proved to inhibit chain reaction of oxidative degradation of polyunsaturated fatty acids integrated in micelles, emulsions, liposomes, low-density lipoproteins (LDL) and animal tissues, which was previously induced by different prooxidans (hydroxyl radicals, iron(II) ions, UV radiation). The extent of lipid peroxidation was mostly evaluated spectrophotometrically, in terms of quantification of thiobarbituric acid-reactive substances as end products -TBARS assay (Blažeković et al, 2010;T. Miura et al, 2000).…”
Section: Chemical-based Antioxidant Assaysmentioning
confidence: 99%